PURIFIKASI DAN KARAKTERISASI FITASE HASIL FERMENTASI Aspergillus niger PADA MEDIA CAIR - . Miswar (Faculty of Agricultural Technology, University of Jember, 2007)
Phytases are enzymes that sequentially remove phosphate groups from myo-inositol 1,2,3,4,5,6-hexakisphosphate (phytate), and are the main storage form of phosphate in plants. It has been produced an extracellular phytase from a wild type Aspergillus niger in a submerged culture. The phytase was purified in two steps by using ammonium sulphate precipitation (0-50% and 50-80% saturation) and DEAE-Cellulose column chromatography. Under these experimental condition, the phytase could be purified at 30 folds. The enzyme showed a maximum catalytic value at pH 5.0 and optimum temperature at 600C. Based on a lineweaver-Burk equation, the purified phytase had the Km and Vmax value by 0.42 mM and 15.2 Pi hour-1 mg protein-1, respectively. The ability of the phytase to hydrolyze phytic acid in maize powder was higher than phytic acid in soybean powder. Keywords: phytase, phytic acid, Aspergillus niger